Tuberculosis Must Fall! : A Multisector Partnership to Address TB in Southern Africa’s Mining Sector - Osewe, Patrick L. (Washington, DC: World Bank, 2018)
This book presents key activities, promising practices, and lessons learned to date from the World Bank’s Tuberculosis (TB) in the Mining Sector Initiative--an innovative multisectoral, multicountry, public-private regional initiative. It examines how a collaborative platform was established to cover 10 southern African countries, and it details the processes through which multiple countries, ministries, sectors, and partners have been brought together to address the varied dimensions of the epidemic.